NUMBER SEVEN AND ITS MEANING IN RELIGIONS- A COMPARATIVE STUDY - Prof. Dr. Khalid Ahmmad Hussein (Scholars Digest Publishing, 2025)
The current research tackles deeply and comprehensively the use of number seven in Holy Quran. This number has specific indications; and it implies certain uses and references when indicated within the religious stories. It highly depends on facts and issues related to the creation of heavens and their numbers. It refers to the number of days in the week which indicates time; as well as a natural phenomenon such as the spectrum, and it may be associated with the treatment of some diseases, and it may be associated with heaven and/or hell and many other associated issues that would be discussed throughout the current study. This topic has been chosen for study and research because of the special nature of this number in general, and in religions in particular.
Keywords: Association, number seven, religious indication, heavens and hell.